2010
DOI: 10.1111/j.1537-2995.2010.02683.x
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining of CD34+ cells from healthy blood donors: development of a rapid and efficient procedure using leukoreduction filters

Abstract: This procedure allows the easy, rapid (<5hr), and efficient preparation of large quantities of CD34+ cells having functional activities similar to those of CD34+ cells from other sources. Therefore, easily available and virally safe, LRFs represent an important and regular WBC source to work with human CD34+ cells, but also with other WBC types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Because both in vitro and ex vivo results suggested that autophagy is required for the full maintenance of LC2 repopulation ability of CML cells incubated in hypoxia, we asked whether it also plays a critical role in normal CD34 + cells. Normal CD34 + cells were purified from leukoreduction filters as described Peytour et al [ 20 ]. Four days after infection, normal CD34 + cells were analyzed for GFP expression and between 35 and 50% of GFP + cells were detected in 3 independent experiments (Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…Because both in vitro and ex vivo results suggested that autophagy is required for the full maintenance of LC2 repopulation ability of CML cells incubated in hypoxia, we asked whether it also plays a critical role in normal CD34 + cells. Normal CD34 + cells were purified from leukoreduction filters as described Peytour et al [ 20 ]. Four days after infection, normal CD34 + cells were analyzed for GFP expression and between 35 and 50% of GFP + cells were detected in 3 independent experiments (Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…These cells are still underutilized in research and medicine most likely due to their low frequency in blood, despite the fact that they are easily accessible without any invasive procedures nor side effects for donors. Moreover our group has shown in previous studies that the use of LRF from different blood donors allows us to obtain enough hematopoietic stem and progenitor cells that is CD34 + cells for research studies (Peytour et al, ; Peytour, Villacreces, Chevaleyre, Ivanovic, & Praloran, ). In the present work, we evidenced some characteristics and functional properties of SSPB HSC.…”
Section: Discussionmentioning
confidence: 99%
“…These rare and relatively old findings suggest that HSCs from SSPB have an interesting biological potential and might be of great interest for research and medicine, as they also represent a readily accessible and safe source of HSCs. In this context, our group recently showed the possibility of using CD34 + cells from SSPB by recycling cells retained on leuko‐reduction filters (LRF) from whole blood samples (Peytour et al, ). We proved that these CD34 + cells contain HSCs with short‐ and long‐term engraftment capacity (Brunet et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Leukocytes were recovered from leukodepletion filters (T2975, Fresenius Kabi, Louviers, France) by counterflow elution as described elsewhere 6 , 19 , 20 with a slight modification, i.e. the cells were flushed directly into 50 mL tubes (Falcon, Dutscher, Brumath, France) (see Online Supplementary Methods ).…”
Section: Methodsmentioning
confidence: 99%